Analisis Struktur Mikro dan Kekerasan Paduan Aluminium ADC 12 Hasil Proses Pengecoran Semi Solid dengan Proses Perlakuan Panas - Syaharuddin Rasyid; Muas M; Ferdian Rosyid; Nursyam Musfirah (Politeknik Negeri Ujung Pandang, 2021)
This research aims to analyze the effect of providing additional heat treatment and artificial aging with variations in temperature of quenching and variations in aging time of ADC12 semi-solid casting result which include hardness and microstructure values. The Selected quenching temperature variations are 10°C, 30°C and 50°C. While the aging time variations are 0 h, 1 h, 3 h, 5 h, 7 h, 9 h, 11 h and 13 h. The tests carried out are hardness testing as well as microstructure that will be used to calculate the grain size values and structural density. The highest hardness value was at 180°C, 10°C cooling media variation with 5 h aging time is 83.10 HB. While the smallest grain size value was at the temperature of 10°C cooling media with an aging time of 5 h is 42.797 µm. The optimal value lies at a temperature of 10°C with an aging time of 5 h resulting hardness 83.7911 HB, the average of grain size is 13.5995 µm and the grain density value is 0.8892 with desirability reaching 0.920.